2007
DOI: 10.1038/sj.gt.3303006
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery by the hSP-B promoter to lung alveolar type II epithelial cells in LAL-knockout mice through bone marrow mesenchymal stem cells

Abstract: Tissue damage and inflammation promote bone marrow stem cells (BMSCs) to differentiate into a variety of cell types in residing tissues. BMSCs can stably maintain their plasticity and are an ideal cell population for delivery of therapeutic genes to non-hematopoietic tissues. Using lacZ as a reporter gene, we demonstrated that the lung-specific human surfactant protein B (hSP-B) 1.5-kb promoter is able to deliver the lacZ gene into the lung of lysosomal acid lipase (LAL) gene-knockout (lalÀ/À) mice by b-galact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…ϪDOX, doxycycline-untreated bitransgenic mice; ϩDOX, doxycycline-treated bitransgenic mice previous study, LAL deficiency caused inflammation-induced BMSC conversion into AT II epithelial cells. 17 Because PPAR␥ serves as a downstream effector of LAL, it is conceivable that BMSC-to-AT II cell conversion is regulated by PPAR␥. To test this assumption, the purified adherent BMSCs from hSP-B 1.5-kb lacZ transgenic mice were injected into 2-month doxycycline-treated or untreated CCSPrtTA/(tetO) 7 -CMV-dnPPAR␥ recipient bitransgenic mice.…”
Section: Bmsc Conversion Into At II Epithelial Cells In the Lung Of Bmentioning
confidence: 99%
See 2 more Smart Citations
“…ϪDOX, doxycycline-untreated bitransgenic mice; ϩDOX, doxycycline-treated bitransgenic mice previous study, LAL deficiency caused inflammation-induced BMSC conversion into AT II epithelial cells. 17 Because PPAR␥ serves as a downstream effector of LAL, it is conceivable that BMSC-to-AT II cell conversion is regulated by PPAR␥. To test this assumption, the purified adherent BMSCs from hSP-B 1.5-kb lacZ transgenic mice were injected into 2-month doxycycline-treated or untreated CCSPrtTA/(tetO) 7 -CMV-dnPPAR␥ recipient bitransgenic mice.…”
Section: Bmsc Conversion Into At II Epithelial Cells In the Lung Of Bmentioning
confidence: 99%
“…17 BMSCs were isolated from femur and tibia of hSP-B 1.5kb lacZ transgenic mice, 2 to 3 months old, 18 and then were cultured in Mesencult MSC basal medium (StemCell Technologies, Vancouver, BC, Canada) at 37°C with 5% CO 2 . After 1 day, the unattached cells were discarded and, for attached BMSCs, the medium was completely replaced.…”
Section: Bone Marrow Stem Cell Injection and Double-immunofluorescencmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow cells were flushed from femurs and resuspended in FACS buffer as previously described. 10 Peripheral blood mononuclear cells were obtained after red blood cell lysis. Lung single cell suspension was prepared as previously described.…”
Section: Flow Cytometric Analysis and Cell Stainingmentioning
confidence: 99%
“…We are the first group to report the combination strategy of Adv-based gene therapy and BMSC-based cell therapy to improve the outcome of islet transplantation. Our data indicated that BMSCs were efficient gene delivery vehicles to improve the outcome of islet transplantation, as they did to treat other diseases [138,139]. Adv-hHGF-hIL-1Ra-transduced primary BMSCs secreted elevated levels of HGF and IL-1Ra and retained their protective capability for the long-term survival of islet grafts.…”
Section: Discussionmentioning
confidence: 72%